Modelling of microstructural effects on the mechanical behavior of ultrafine-grained Nickel using crystal plasticity finite element model. (September 2015) - Phan, Van-Tung; Nguyen, Thê-Duong; Bui, Quang-Hien; Dirras, Guy
Abstract: In this contribution, a crystal plasticity finite element model (CPFEM) is revisited to study the microstructural influence on macroscopic mechanical behavior of ultrafine-grained (UFG) Nickels processed by two different powder metallurgy methods: Hot isostatic pressing (HIP) and spark plasma sintering (SPS). In addition, a modified Hall–Petch relationship is used at the grain level to investigate both grain size and oxide phase dependence of UFG materials mechanical behavior. Within the framework of small strain hypothesis, grain scale simulations of the UFG face centered cubic (FCC) Nickel are performed by applying the CPFEM accounting for the experimental grain orientation data at the integration points. A good agreement between experimental and numerical results is achieved.